Development of Mobile Cloud Applications using UML - Dong Kwan Kim (Institute of Advanced Engineering and Science, 2018)
With the proliferation of cloud computing technologies, smartphone users are able to use a variety of cloud computing-based mobile services such as games, education, entertainment, and social networking. Despite the popularity of such a mobile cloud computing, the complicated multi-tier system configuration of the mobile application must be one of the major impediments to develop mobile cloud applications. This paper presents development processes and procedures for developing mobile cloud applications by effectively applying Unified Modeling Language (UML), a representative object-oriented modeling language. The paper is intended to enhance the development productivity of the mobile cloud application and to improve the effectiveness of communication between software developers. In addition, we used the Android mobile platform and Amazon Web Service for cloud computing in order to demonstrate the applicability of the proposed approach to systematically apply the UML profiles and diagrams for cloud-based mobile applications.